Loss of IκB kinase β promotes myofibroblast transformation and senescence through activation of the ROS-TGFβ autocrine loop. Issue 5 (5th March 2016) - Chen, Liang; Peng, Zhimin; Meng, Qinghang; Mongan, Maureen; Wang, Jingcai; Sartor, Maureen; Chen, Jing; Niu, Liang; Medvedovic, Mario; Kao, Winston; Xia, Ying
Abstract: Using forward and reverse genetics and global gene expression analyses, we explored the crosstalk between the Iκ B kinase β (IKKβ) and the transforming growth factor β (TGFβ) signaling pathways. We show that in vitro ablation of Ikkβ in fibroblasts led to progressive ROS accumulation and TGFβ activation, and ultimately accelerated cell migration, fibroblast-myofibroblast transformation and senescence. Mechanistically, the basal IKKβ activity was required for anti-oxidant gene expression and redox homeostasis. Lacking this activity, IKKβ-null cells showed ROS accumulation and activation of stress-sensitive transcription factor AP-1/c-Jun. AP-1/c-Jun activation led to up-regulation of the Tgfβ2 promoter, which in turn further potentiated intracellular ROS through the induction of NADPH oxidase (NOX). These data suggest that by blocking the autocrine amplification of a ROS-TGFβ loop IKKβ plays a crucial role in the prevention of fibroblast-myofibroblast transformation and senescence.